Educational Potential of Using Elements of Folk Applied Art in Fine Arts Education - Muzropova Guljamol Mardonovna (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2025)
Abstract: This article explores the educational potential of incorporating elements of folk applied art into fine arts education. Folk art represents the cultural heritage, traditions, and aesthetic values of a community and serves as a vital resource for developing students’ creativity, cultural awareness, and practical artistic skills. Integrating folk applied art into teaching enhances learners’ understanding of historical and cultural contexts, promotes national identity, and fosters respect for diverse cultural expressions.